Age and petrogenesis of the beryl-bearing granitic magmatism of the Velasco Pegmatite District, Pampeana Province, NW Argentina - Sardi, Fernando Guillermo (2021)
Two porphyritic granitoids (Huaco and Sanagasta) in the Velasco district of the Pampeana Pegmatite Province in Northwestern Argentina are recognized. They are considered the fertile granites of the beryl-bearing pegmatites and can be described as post-orogenic and peraluminous A-type granites formed in an intraplate tectonic setting during an extensive regime, whose magma source is predominantly of cortical origin and to a lesser extent, mantle-derived. The pegmatites are classified as Rare Elements of the beryl type and beryl-columbite-phosphate subtype, while the entire district shows characteristics related to the NYF (Nb-Y-F) petrogenetic family. From rocks and cogenetic minerals of an individual ‘Ismiango’ pegmatite of the Velasco district, two Rb/Sr isochrons have been constructed. They define an age of 330.3 ± 8.3 and 331.7 ± 2.3 Ma and fall in the Lower Carboniferous period, consistent with the age of the parental and host-rock, the Huaco granite. As the Ismiango pegmatite has a similar composition and structure to the other beryl mineralized pegmatites of the Velasco district, the obtained age is attributed extensively for the entire district. According to the initial 87Sr/86Sr value obtained of 0.713, the pegmatite-magmatism of the Velasco District might be mainly derived from the crust with some minor participation of mantle materials.